Pricing approximations and error estimates for local Lévy-type models with default. (May 2015) - Lorig, Matthew; Pagliarani, Stefano; Pascucci, Andrea
Abstract We find approximate solutions of partial integro-differential equations, which arise in financial models when defaultable assets are described by general scalar Lévy-type stochastic processes. We derive rigorous error bounds for the approximate solutions. We also provide numerical examples illustrating the usefulness and versatility of our methods in a variety of financial settings.